O papel do inglês e do pomerano na construção de identidade em comunidades pomeranas do ES - Pinheiro, Lívia Melina da Silva (2018)
This study aims to reflect upon the role of English and Pomeranian in the process of identity construction in Pomeranian communities in the state of Espirito Santo, Brazil. The additional languages analyzed in this study were English, (as a foreign language) and Pomeranian (as a language of inheritance) and Portuguese as the official language in Brazil. In order to reach this goal, the study analyzed a corpus composed of dissertations and theses published over the last five years and that dealt with language policies, bilingualism, and the teaching of Pomeranian and English in Pomeranian communities. A total of eleven master theses and three PhD dissertations composed the corpus of this study/thesis. The theoretical framework was based on Bauman's concept of identity and Bourdieu's concept of symbolic and cultural capital. The analysis of the corpus indicates a gap in studies carried out in these communities, specifically related to the teaching of English and Pomeranian. Most of the works analyzed in the corpus aimed to value the Pomeranian language and culture for preservation purposes. The review of language policies suggests that the status of English in Brazil today reflects Bourdieu's theories of cultural, market, and symbolic capital. Bauman's concept of identity, analyzed in relation to the role of English, Pomeranian and Portuguese, suggests that these languages should be taught in these communities, respecting global and local differences and needs in order to provide the feeling of local, national, and global belonging; as well as to promote the Brazilian-Pomeranian identity in these communities.